Interfacial Diffusion during Growth of SnO2(110) on TiO2(110) by Oxygen Plasma Assisted Molecular Beam Epitaxy - Palgrave, R; Bourlange, A; Payne, D; Foord, J; Egdell, R (2009)
Oxygen plasma-assisted molecular beam epitaxy was used to grow layers of SnO2 on single-crystal ratile TiO2 (110) substrates. Surface composition was studied by X-ray photoelectron spectroscopy, whereas secondary ion mass spectrometry was used to determine the depth distribution of Sn and Ti. For substrate temperatures below 600 °C, SnO2 grows as an epitaxial film on top of the TiO2, but at higher temperatures there is evidence for pronounced interdiffusion between the substrate and the epilayer. At growth temperatures above 775 °C the Sn diffuses rapidly into the substrate to give Sn-doped TiO2 rather than a distinct SnO 2 epilayer. The films were all highly (110) oriented but the lattice parameter of the deposited film decreased with increasing growth temperature, consistent with the formation of TixSn1-xO2 solid solutions through interfacial solid-state reaction in a narrow temperature regime between 750 and 775 °C. © 2009 American Chemical Society.